2021
DOI: 10.1186/s12942-020-00254-w
|View full text |Cite
|
Sign up to set email alerts
|

Children’s outdoor active mobility behaviour and neighbourhood safety: a systematic review in measurement methods and future research directions

Abstract: Background Numerous studies have examined the association between safety and primary school-aged children’s forms of active mobility. However, variations in studies’ measurement methods and the elements addressed have contributed to inconsistencies in research outcomes, which may be forming a barrier to advancing researchers’ knowledge about this field. To assess where current research stands, we have synthesised the methodological measures in studies that examined the effects of neighbourhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Our methodological quality assessment revealed that most studies fulfilled elements relevant to studies reporting but essentially lacked addressing components in the design, method of measurement, and analysis for evidence-based research on children's active health. 32 This may have resulted in the majority of studies were of moderate and poor quality. Subjective measures using questionnaires rely on human recall distant events.…”
Section: Methodological Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…Our methodological quality assessment revealed that most studies fulfilled elements relevant to studies reporting but essentially lacked addressing components in the design, method of measurement, and analysis for evidence-based research on children's active health. 32 This may have resulted in the majority of studies were of moderate and poor quality. Subjective measures using questionnaires rely on human recall distant events.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…65 Yet, we found some inconsistencies among studies employing objective measures. Although a review of measurement methods is out of the scope of this paper, the discrepancies in some of the outcome necessitate highlighting some critical research challenges for future research attention yet were elaborated further elsewhere by Zougheibe et al 32 Study design is likely to affect the outcome. Longitudinal studies limit selection bias associated with cross-sectional design.…”
Section: Methodological Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of research on crime-related determinants of ACS has centered on parental perceptions of crime, which are consistently indirectly associated with children's ACS behavior [12][13][14]. However, only two studies with inconsistent findings have examined associations between police-reported crime and ACS [14,15].…”
Section: Introductionmentioning
confidence: 99%